Improving the System of Organization and Standardization of Social Services - Khurshida Abdumalikovna Karjavova (Periodica Journal, 2022)
This article is about the improvement of the system of organization and standardization of the provision of social services, it also focuses on social services and their origin, types, quality and control of services.
Keywords: services; standardization; system; customer